The Effect of the Snowball Throwing Learning Model on Fourth-Grade Students' Indonesian Language Learning Outcomes in Generating Questions from Reading Passages at SD Negeri 040443 Kabanjahe, Academic Year 2025/2026 - Asti Puspita Br Sembiring; Yunistita Singarimbun; Nurlia Ginting (Asian Journal of Applied Education (AJAE), 2026)
This study aims to analyze the effectiveness of implementing the Snowball Throwing learning model in improving Indonesian Language learning outcomes on the topic of composing questions based on reading passages among fourth-grade students at SD Negeri 040443 Kabanjahe in the 2025/2026 Academic Year. The study employed a quantitative approach with a pretest-posttest control group design. The research subjects consisted of 50 students, with class IV A as the experimental group and class IV B as the control group. The data collection instrument was an objective multiple-choice test that had met the validity and reliability criteria. The research data were analyzed using normality tests, homogeneity tests, and hypothesis testing to determine differences in learning outcomes between the groups. The results showed that the average learning outcome score of students in the experimental class reached 93.2, which was higher than the control class with an average score of 68.0. These findings indicate that the implementation of the Snowball Throwing learning model is effective in improving students' Indonesian Language learning outcomes.